PENCEGAHAN DAN PENANGGULANGAN MALARIA PADA MASYARAKAT DI KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - Harpenas Harpenas; Muh. Syafar; Hasanuddin Ishak (Politeknik Kesehatan Kemenkes Mamuju, 2016)
The aim of the research is to give a description on the prevention and handling of malaria. The research used qualitative method with a phenomenology approach. The informants consisted of 11 native people of Mamuju and Trasnmigrants selected by using snow ball technique.The results of the research reveal that in general community diagnoses malaria based on trias of malaria which tends be treated by themselves. To prevent the bites of mosquitoes at night, the community use mosquitoes nets bought in the markets with their own money. Prevention activities on the occurrence of mosquitoes breeding done by hoarding/drainage for flooded area are generally good but in transmigration area and original area Mamuju they do not run well.